Development of 5G Communication in the Tropical Regions with a Link Budget - Trilochan Patra; Swarup Kumar Mitra (Advanced Aspects of Engineering Research Vol. 6, 2021)
The principal characteristic of tropical regions is that the torrential rain occurs almost throughout the year. As a result of this torrential rain, the signals of these areas get attenuated causing disruption in transmitting important messages from a transmitter to a receiver. So the people of these regions face a lot of obstacles in their field of wireless communication. To overcome these obstacles many researchers and developers have been trying heart and soul for a long time by using 5G communication. But no fruitful result has yet been obtained for this purpose. So the goal of this work is to remove these obstacles by using diversity techniques through 5G communication. To achieve the desired result multiple-input and multiple-output (MIMO) technique has been adopted as an antenna diversity technique and here this technique has been used in the communication link model designed for 5G communication for tropical regions. Here a link budget for the designed communication link model has been laid down to increase the signal power and signal to noise ratio (SNR) at the receiver. The link budget depends on different parameters and these parameters have been demonstrated in this work. In this work an experimental data sheet has also been adopted to achieve the desired result of the link budget.